A Homeopathic View of the Influence of Chronic Diseases in the Manifestation of COVID-19 - da Costa Fujino, Fernanda Maria Simões; Olandim, Ana Amélia Campos Claro; Barnabé, Vagner Doja; Coggan, Jennifer Anne; Benites, Nilson Roberti (Homeopathy, 2021)
COVID-19 (coronavirus disease 2019) may present variable symptoms among infected individuals, with chronic disease patients appearing as the group most susceptible to present severe pulmonary infection, while having a higher risk of developing complications from the disease. This study demonstrates the relationship between the manifestation of COVID-19 and the presence of chronic miasmatic disease, based on the works of Samuel Hahnemann. The reaction of the individual who previously presented chronic miasmatic disease, when in contact with the stimulus of the epidemic disease, depends on the type of response that the organism was generating in the face of the pre-existing situation: if it is an intense reaction and greater than that which the stimulus of COVID-19 can generate, this individual will not develop the severe form of the epidemic disease; if the reaction is less than that generated by COVID-19, more intense symptoms may appear. Understanding that the presence of a chronic miasmatic disease interferes with the manifestation of COVID-19, which may have repercussions on other organs, can change how one must act on the treatment, as this can alter the individual's health status.
Keywords: COVID-19; homeopathy; chronic disease